(untitled) (Jurnal Vokasi Mekanika, 2025)
The main problems in this research are: (1) How does independence influence student learning outcomes? (2) How does discipline influence student learning outcomes, and (3) How does independence and discipline influence student learning outcomes. The objectives of this research were designed to: (1) To determine the increase in student independence regarding learning outcomes in the SMAW welding subject class XI TLAS at SMK Negeri 2 Bengkulu City. (2) To determine the increase in student discipline towards learning outcomes in the SMAW welding subject class Negeri 2 Bengkulu City. This research applies a correlational method. The sample for the research carried out was 16 students of class XI TLAS SMK Negeri 2 Bengkulu City. The independence and discipline questionnaire uses a Likert scale and test questions to collect data. Data were analyzed through correlation analysis and multiple regression. Student independence has the strongest correlation with learning outcomes (0.613), followed by discipline (0.589). The significant relationship between independence and discipline on learning outcomes (0.681) shows that these two variables complement each other. The conclusion from this research is that independence and discipline have a significant influence on student learning outcomes